O papel moderador das comunidades virtuais de marca e de interesse: um modelo teórico sobre a influência da incongruência no engajamento e seus efeitos - Rohde, Juliana Plocharski Pedroso (Universidade do Vale do Rio dos Sinos, 2022)
This research aimed to analyze the context of virtual communities. Its main objective was to investigate the moderating effect of the type of virtual community, brand or interest, on the engagement and behavioral intention of the consumer participating in virtual communities. This work also added to this context the investigation of the effects of incongruent stimuli when used in virtual community environments. Incongruity was inserted in this work through the Schema Incongruity Processing Theory (SIPT), Mandler (1983). The theory seeks to understand the ways of processing incongruence, determining levels of incongruity and its responses to affective levels according to the resolution by assimilation or accommodation of information and, until then, it had only been used in offline advertising contexts. The objective of this work was reached after a survey operationalization, the final sample of 328 respondents was obtained. The measurement model was verified and validated through the technique of confirmatory factor analysis (CFA) and analysis of convergent and discriminant validity. The structural model and the generated hypotheses were tested through structural equation analysis (SEM). The model analysis showed a positive relationship between incongruity and the trust, however, it did not show a direct relationship between incongruity and the engagement and commitment constructs. On the other hand, the relationships between the trust and commitment constructs showed a positive relationship with the engagement construct. Finishing the analysis of the proposed direct relationships, the engagement construct showed a positive relationship when analyzing its direct impact on behavioral intention and also on the word-of-mouth construct. Finally, the analysis of the ‘community type’ moderating effect was not considered significant.
Keywords: Teoria da incongruência; Engajamento; Comunidade virtual de marca; Comunidade virtual de interesse; Incongruity theory; Engagement; Virtual brand community; Virtual community of interest; ACCNPQ::Ciências Sociais Aplicadas::Administração